Using advocacy and data to strengthen political accountability in maternal and newborn health in Africa. Issue 3 (15th October 2016) - ten Hoope‐Bender, Petra; Martin Hilber, Adriane; Nove, Andrea; Bandali, Sarah; Nam, Sara; Armstrong, Corinne; Ahmed Mohammed Ahmed,; Chatuluka, Mathias G.; Magoma, Moke; Hulton, Louise
Abstract: Accountability mechanisms help governments and development partners fulfill the promises and commitments they make to global initiatives such as the Millennium Development Goals and the Global Strategy on Women's and Children's health, and regional or national strategies such as the Campaign for the Accelerated Reduction in Maternal Mortality in Africa (CARMMA). But without directed pressure, comparative data and tools to provide insight into successes, failures, and overall results, accountability fails. The analysis of accountability mechanisms in five countries supported by the Evidence for Action program shows that accountability is most effective when it is connected across global and national levels; civil society has a central and independent role; proactive, immediate and targeted implementation mechanisms are funded from the start; advocacy for accountability is combined with local outreach activities such as blood drives; local and national champions (Presidents, First Ladies, Ministers) help draw public attention to government performance; scorecards are developed to provide insight into performance and highlight necessary improvements; and politicians at subnational level are supported by national leaders to effect change. Under the Sustainable Development Goals, accountability and advocacy supported by global and regional intergovernmental organizations, constantly monitored and with commensurate retribution for nonperformance will remain essential.